BROMATOLOGICAL AND SENSORIAL EVALUATION OF PERESKIA ACULEATA USE IN PASTA DOUGH - Cremasco, C. P.; Godinho, A. M. M.; Boso, A. C. M. R.; Vilas Boas, A. C. S.; Mollo Neto, M.; Gabriel Filho, L. R. A. (Revista Brasileira de Engenharia de Biossistemas, 2016)
The aim of this study was to analyze and study the nutritional quality of vegetables ora-pro-nobis (Pereskia aculeata). It is a shrub, where its leaves can be used to supplement the power of low-income people and animals, as well as to serve as decorations and protective fences. The non-traditional vegetables can be an alternative to combat malnutrition. As they are good sources of nutrients, easily grown and have a low market value. In this work have been formulated masses with the plant in question and evaluated how much to its acceptability. The study showed that the ora-pro-nobis presents considerable crude protein and mineral matter. The sensory test showed a great acceptability of the formulated mass with the plant.